Vascular angular remodeling by kissing-Y stenting in wide necked intracranial bifurcation aneurysms. (5th December 2016) - Melber, Katharina; Meila, Dan; Draheim, Philipp; Grieb, Dominik; Greling, Björn; Schlunz-Hendann, Martin; Brassel, Friedhelm
Abstract : Introduction: Single stent deployment leads to a change in vascular geometry in wide necked bifurcation aneurysms. In some complex cases, the use of the single stent technique might not be sufficient or may not be feasible. The kissing-Y stenting technique appears to be an alternative endovascular treatment option. The aim of this study was to evaluate the effects of the kissing-Y stenting technique on vascular angular remodeling. Methods: 21 patients with wide necked intracranial bifurcation aneurysms at different sites (10 anterior communicating artery, 6 middle cerebral artery, 3 basilar artery, 1 vertebral artery/posterior inferior cerebellar artery, 1 internal carotid artery/posterior communicating artery) were treated with 44 closed cell stents (follow-up 2012–2016) using the kissing-Y stenting technique. We analyzed vascular angle geometry between the mother and both affected daughter vessels by digital subtraction angiography, before and after stent deployment, using standard working projections. Results: Endovascular treatment of wide necked intracranial aneurysms using the kissing-Y stenting technique significantly decreased the angle between the bifurcation branches from 130.4±9.5° to 91.5±9.1° (p<0.0001). Conclusions: Kissing-Y stenting in wide necked bifurcation aneurysms leads to vascular angular remodeling of both affected branches. The resulting straightening of the bifurcation angle may prevent aneurysmal recurrence.